(3cJGH HGddZI GdJQcjIs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje SjGS jbGS s
(3BNQgG (B:s
(3efbWY ThO GdMeO ddg ChdkG hBNQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdcJGH ecJhH HGddZI GdJQcjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdMLjGJ (B_ (3GdehUd (B(21) s
Keywords: (3GdeLGejYs